Answer: y=-x+4
Step-by-step explanation:
Answer:
![{ax}^{3} + 4ax \\](https://tex.z-dn.net/?f=%20%7Bax%7D%5E%7B3%7D%20%20%2B%204ax%20%5C%5C%20%20)
factorise out a and x :
![{ \boxed{answer{= ax( {x}^{2} + 4) }}}\\ but \: farther \: more : \\ = ax( {x}^{2} + {2}^{2} )](https://tex.z-dn.net/?f=%20%7B%20%5Cboxed%7Banswer%7B%3D%20ax%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%204%29%20%7D%7D%7D%5C%5C%20but%20%5C%3A%20farther%20%5C%3A%20more%20%3A%20%20%5C%5C%20%20%3D%20ax%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7B2%7D%5E%7B2%7D%20%29)
but from general factorization:
![{ \boxed{( {a}^{2} + {b}^{2}) = {(a + b)}^{2} - 2ab }}](https://tex.z-dn.net/?f=%7B%20%5Cboxed%7B%28%20%7Ba%7D%5E%7B2%7D%20%2B%20%20%7Bb%7D%5E%7B2%7D%29%20%3D%20%20%7B%28a%20%2B%20b%29%7D%5E%7B2%7D%20%20%20-%202ab%20%7D%7D)
a » x
b » 2
therefore:
![= ax \{ {(x + 2)}^{2} - 2(x)(2) \} \\ \\ = { \boxed{ \boxed{ax( {x + 2)}^{2} - 4x }}}](https://tex.z-dn.net/?f=%20%3D%20ax%20%5C%7B%20%7B%28x%20%2B%202%29%7D%5E%7B2%7D%20%20-%202%28x%29%282%29%20%5C%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%7B%20%5Cboxed%7B%20%5Cboxed%7Bax%28%20%7Bx%20%2B%202%29%7D%5E%7B2%7D%20-%204x%20%7D%7D%7D)
Answer:
a = 55/6
Step-by-step explanation:
<u>Solving in steps:</u>
- 3/5a = 5 1/2
- 3/5a = 11/2
- a = 11/2 : 3/5
- a = 11/2*5/3
- a = 55/6 or 9 1/6